Effects of inhaled ceramic fibres on macrophage function of rat lungs. Issue 1 (January 1994) - Morimoto, Y; Yamato, H; Kido, M; Tanaka, I; Higashi, T; Fujino, A; Yokosaki, Y
Abstract : To evaluate the biological effect of ceramic fibres on the clearance function of alveolar macrophages (AMs) morphological changes and phagocytic activity of AMs were assessed. Rats were exposed to respirable ceramic fibres with a mass median aerodynamic diameter of 4.4 microns and a concentration of 20.1 mg/m3 in an exposure chamber. They were killed after one week (group A) and two weeks (group B) of exposure, and four weeks (group C) and 12 weeks (group D) after exposure for two weeks. The AMs recovered by bronchoalveolar lavage (BAL) from each test group were incubated with yeast and phagocytic activity was determined by counting the number of yeast cells in AMs. Morphological features of AMs were assessed by scanning electron microscopy and quantified according to morphological changes. Total cell counts in BAL fluid from exposed rats in group A were higher than in control rats. Phagocytic activity of exposed AMs in group B and C exceeded that of control AMs. Morphological changes of the exposed AMs in groups A, B, and C were greater than those of control AMs. These findings suggest that ceramic fibres induced the phagocytic activity and morphological changes in AMs, and that the clearance function of AMs was stimulated by the inhaled ceramic fibres.